CCB RETENTION AND PENETRATION IN EUCALYPTUS FENCE POSTS IN FUNCTION OF CONDITION OF PRESERVATIVE TREATMENT - Lima, Pedro Augusto Fonseca; Gouveia, Fernando Nunes; Baraúna, Edy Eime Pereira; Sette Jr, Carlos Roberto (Floresta, 2020)
The objective of this work was to evaluate the efficiency of the industrial preservative treatment with Chromated Copper Borate (CCB) in different concentrations and pressure time in the autoclave through retention and penetration in Eucalyptus wood. Nine Eucalyptus trees were felled, debarking and cut into fence posts with a length of 2.20 meters and diameters ranging from 9.2 to 15.4 cm. The Eucalyptus fence posts were submitted to the industrial autoclave (Bethel method) in nine conditions, according to the CCB concentration and the pressure times: 1.5%, 2.0%, and 2.5% and 30, 60 and 90 minutes. The retention and penetration tests were performed. The application of 1.5% CCB concentration and 30 minutes of pressure in the autoclave provided penetration and retention according to the levels required for the application of the wood as fence posts in contact with the soil, and is the conditions indicated for the treatment E. urograndis wood preservative with CCB.